From Spirituality to Mechanical Solidarity: The Role of Religious Communities in Addressing Homelessness - Masroer; Moh. Frendi Wijaya (International Journal of Sociology of Religion, 2026)
Homelessness is a form of social inequality that remains a problem in Yogyakarta. This study examines the role of religious communities, both majority and minority, in assisting the homeless through spiritual approaches and social action, and its implications for public policy. Using a qualitative case study method over three months, data was collected through interviews, observations, and documentation, then analyzed thematically. The results indicate that religious communities contribute through food assistance and moral support, which has a positive impact on the psychological and spiritual well-being of the homeless. However, this assistance is still charitable in nature and has not been integrated with government policy, thus failing to address the root causes of homelessness. Key obstacles include limited data collection, weak collaboration across religious communities, and stigma against minority groups. This study concludes that spirituality can be a force for promoting social justice if supported by inclusive and collaborative public policies.